Evaluating the Effectiveness of Graduated Stress Exposure in Virtual Spaceflight Hazard Training. (December 2018) - Finseth, Tor T.; Keren, Nir; Dorneich, Michael C.; Franke, Warren D.; Anderson, Clayton C.; Shelley, Mack C.
Psychological and physiological stress experienced by astronauts can pose risks to mission success. In clinical settings, gradually increasing stressors help patients develop resilience. It is unclear whether graduated stress exposure can affect responses to acute stressors during spaceflight. This study evaluated psychophysiological responses to potentially catastrophic spaceflight operation, with and without graduated stress exposure, using a virtual reality environment. Twenty healthy participants were tasked with locating a fire on a virtual International Space Station (VR-ISS). After orientation, the treatment group ( n = 10) practiced searching for a fire while exposed to a low-level stressor (light smoke), while the control group ( n = 10) practiced without smoke. In the testing session, both groups responded to a fire while the VR-ISS unexpectedly filled with heavy smoke. Heart rate variability and blood pressure were measured continuously. Subjective workload was evaluated with the NASA Task Load Index, stress with the Short Stress State Questionnaire, and stress exposure with time-to-complete. During the heavy smoke condition, the control group showed parasympathetic withdrawal, indicating a mild stress response. The treatment group retained parasympathetic control. Thus, graduated stress exposure may enhance allostasis and relaxation behavior when confronted with a subsequent stressful condition.